Maps Matter. The 10/40 Window and Missionary Geography - Korte, Hannah de (Exchange, 2020)
The 10/40 Window map is used by evangelical missionary societies to promote mission in Northern Africa, the Middle East and South East Asia. It has been widely popular among Christians worldwide, but has also suffered sustained criticism. The map itself, however, has received no scholarly attention. This article investigates the 10/40 Window map through the lens of the concept of territoriality. Using insights from the field of critical cartography, it argues that the map is pivotal in directing missionary zeal, but that in turn it has also reshaped missionary thinking. This is so because the actual map’s metageographical proportions, its cartographic language and the accompanying rhetoric communicate several novel key propositions about mission. The overall argument of this article is that maps are not innocuous illustrations, but indeed that maps matter a great deal and that missionary geography should be taken seriously.